Radiological Anatomy of the Extremities and Back - Penprapa Klinkhachorn; Powsiri Klinkhachorn; Robert Tallaksen; Terance Wijesinghe; Daniel Sloan; Frank Reilly (Association of American Medical Colleges, 2010)
Abstract This tutorial serves as an introduction to normal radiographic anatomy of the extremities and back for preclinical students enrolled in medical human structure. It is composed of high-quality radiographs containing comprehensive labeling of bony structures. Image resolution exceeds that found in many more conventional learning resources such as textbooks, dissectors, and atlases. Images were digitized to stimulate self-directed study by integrating introductory radiographic anatomy into a structured format that is readily accessible for local and distance learning. Active learning was achieved by creating three tutorial units that provide learners with opportunities for repetition and self-assessment through immediate feedback and quizzes on labeled structures. The tutorial is best used in conjunction with radiology/anatomy lectures and labs to reinforce the didactic and practical experiences for learners enrolled in human anatomy courses. Organizing content into discrete tutorials is highly effective in teaching learners a large volume of information without overwhelming them all at once. Framing content in a clinically relevant manner not only serves to solidify what students have learned in their courses but also creates confidence by demonstrating how they will approach patient problems in their clinical years. This resource is completely self-contained and assigned for self-directed learning during the weeks when content is taught to preclinical students in human structure.